Bahasa Indonesia dalam Akuntansi: Tantangan dan Solusi (Studi Kasus pada Mahasiswa Akuntansi Universitas Negeri Medan) - Situmorang, Donestine Laurensia; Donna Ladies Simanjuntak; Marcelina Uli Arta Br Nainggolan; Sebastian Sirait; Tien Maria Lubis; Ayu Nadira Wulandari (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The use and understanding of Indonesian is an important aspect for the continuity of the learning process, especially in accounting learning. This research comprehensively investigates the challenges and solutions related to the use of Indonesian in accounting learning among accounting students at Medan State University. This research uses case studies to understand what challenges and difficulties students face in learning accounting and what solutions are provided to overcome these problems and provide students with an idea of what to expect. The subjects of this research were all accounting students from the classes of 2022, 2023 and 2024, Medan State University. The method used in the research is qualitative research with a descriptive approach in data analysis. The results obtained were that some students experienced difficulties in learning accounting due to language differences and the use of foreign languages in accounting terms as well as students' lack of understanding and knowledge of standard Indonesian language and being good at constructing logical and coherent sentences. Students hope for the development of teaching materials, standard and good Indonesian language training as well as literacy, and familiarization in an effort to improve Indonesian language skills for accounting students at Medan State University. It is hoped that the research findings can contribute to the development of the accounting curriculum and improve the quality of Indonesian language learning in higher education environments.